(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Coyote is often viewed as the archetypal trickster symbol with misdeeds and foolhardy behavior. Here, in the present Jungian psychological research, the Coyote is decoded as a cultural-socialization agent and a cultural hero. Coyote as the libidinal life-force’s flow, guides the masculine and the feminine representation in the society, carrying the cultural legacy yet manifesting, shaping socio-cultural roles progressively. A Northern Paiute tribe Coyote myth is selected in this paper, reflected and investigated through the interdisciplinary prism and Jungian research tool of archetypal amplification. It resulted in understanding the existential expression, identity, cultural legacy, traditions, representation of male-female roles and the functioning of society as well as its culture at large, through the acts and learnings of the archetypal hero. This myth is also a dive into the collective memoir of the historical precedents of the Native American tribal movement, settlements and identity struggles indicated through the latent symbols of the physical problems of the Coyote and the granddaughter in the myth.